Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Sumber Daya Manusia di SMK Negeri 1 Demak - Fatkhur Roziqin; Henry Yuliamir (Mahesa Research Center, 2026)
This study aims to analyze the influence of work environment and work motivation on the performance of human resources (HR) at SMK Negeri 1 Demak. The research background is based on variations in the performance of teachers and education staff, which are presumed to be related to the condition of the work environment and the level of employee motivation. This research employs a quantitative approach with an explanatory research design. The study population consists of 67 employees, of which 66 respondents were used as the sample through a saturated sampling (census) technique. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability and analyzed using multiple linear regression. The findings indicate that: (1) the work environment has a positive and significant effect on HR performance, with a t-value of 2.842 and a regression coefficient of 0.312; (2) work motivation has a positive and significant effect and is the most dominant factor, with a t-value of 5.412 and a regression coefficient of 0.478; and (3) the work environment and work motivation simultaneously have a significant effect on HR performance, with an F-value of 42.318 and a contribution of 56.9%. Meanwhile, 43.1% of HR performance is influenced by other factors outside the scope of this study, such as leadership, competence, organizational culture, and workload. The study concludes that improving HR performance at SMK Negeri 1 Demak requires continuous enhancement of the work environment and strengthening employee motivation. The implications of the research highlight the importance of improving work facilities, providing performance appreciation, strengthening leadership development, and promoting continuous professional development to support employee performance effectiveness.